1994
DOI: 10.1180/claymin.1994.029.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Variation in kaolinite morphology with growth temperature in isotopically mixed pore-fluids, Brent Group, UK North Sea

Abstract: A B ST R ACT: Diagenetic kaolinite in reservoir sandstones of the Brent Group precipitated following the dissolution of detrial feldspar. Two distinct morphologies of kaolinite occur: (1) early diagenetic vermiform kaolinite which is often associated with expanded detrital micas: (2) later diagenetic 'blocky" kaolinite. Combined hydrogen and oxygen isotopic studies suggest that vermiform kaolinite precipitated at 25-50~ and blocky kaolinite at 50-80~ from pore-waters of a similar isotopic composition (6t'~O 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…In addition to the relationship between morphology and temperature of precipitation discussed above, previous isotopic studies of kaolin in sandstones have also demonstrated a direct correlation between morphology and isotope chemistry. In a compilation of North Sea data, Osborne et al (1994) noted that low temperature 'vermiform' kaolinite was characterized by high O values and strongly depleted D. Similar kaolinite compositions were noted in upper Jurassic reservoir sandstones from the Magnus Province, east Shetland Basin (Fallick et al 1993). Higher temperature polytypes of kaolin, including samples described as kaolinite (McAuley et al 1994), 'blocky' or 'intermediate' kaolinite (Glassman et al 1989) and dickite (McAuley et al 1994) (Fig.…”
Section: Stable Isotope Analysis Of Kaolinmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to the relationship between morphology and temperature of precipitation discussed above, previous isotopic studies of kaolin in sandstones have also demonstrated a direct correlation between morphology and isotope chemistry. In a compilation of North Sea data, Osborne et al (1994) noted that low temperature 'vermiform' kaolinite was characterized by high O values and strongly depleted D. Similar kaolinite compositions were noted in upper Jurassic reservoir sandstones from the Magnus Province, east Shetland Basin (Fallick et al 1993). Higher temperature polytypes of kaolin, including samples described as kaolinite (McAuley et al 1994), 'blocky' or 'intermediate' kaolinite (Glassman et al 1989) and dickite (McAuley et al 1994) (Fig.…”
Section: Stable Isotope Analysis Of Kaolinmentioning
confidence: 97%
“…As feldspar dissolves during progressive burial, kaolin morphologies coarsen and become more euhedral due to recrystallization. Kaolinite coarsened by recrystallization (and intergrowths of kaolinite with dickite pseudomorphing kaolinite) are commonly referred to in the literature as 'blocky' or 'intermediate' kaolinite (Osborne et al 1994;Beaufort et al 1998). Intermediate kaolinite may, however, form by hydrothermal processes involving the illitization of early kaolinite by hot fluids (Lanson et al 1996), as well as by burial-related recrystallization.…”
Section: Sem and Xrd Studies Of Kaolin Polytypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre lim i nary al ter ation stages of un sta ble com ponents of the grain fab ric (such as micas and feld spars) led to the kaolinite for ma tion. Tem per a tures of the kaolinite for ma tion may be de ter mined as 25-50°C (Osborne et al, 1994). The pre cip i tation of sil ica may have also started at this tem per a ture.…”
Section: Interpretation and Discussion Evolutionary Pathways Of Diagementioning
confidence: 99%
“…5G). Kaolinite forms in an acidic en vi ron ment (Osborne et al, 1994) where a sig nif i cant role is played by mete oric wa ters, slightly acidic due to dis so lu tion of CO 2 and organic ac ids (Giles and de Boer, 1990). Dur ing the change from suboxic to anoxic con di tions, berthierine is re placed by py rite in the zone of sul phate re duc tion.…”
Section: Origin Of Berthierinementioning
confidence: 99%